College Women's Gender Identity and Their Drinking Choices - Likis‐Werle, Elizabeth (Journal of addictions & offender counseling, 2017)
Because college women's drinking rates now rival men's rates, the authors interviewed college women to ascertain how gender identity affected their drinking choices. Interpretative phenomenological analysis indicated that high-risk drinkers viewed their gender identity differently than did low-risk drinkers. Counseling implications are discussed.